ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC ADMINISTRATIVE PROCESSES IN BRAZIL AFTER THE ACCESS TO INFORMATION LAW: ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC ADMINISTRATIVE PROCESSES IN BRAZIL AFTER THE LAW ON ACCESS TO INFORMATION - Souza, Virgínia Waleska Oliveira Machado de; Patrocinio Gomes, Vanielle Aparecida; Pozo, Osmar Vicente Chevez; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
In order to achieve success in the provision of services, the Public Administration sought to adapt to the new demands of the Information Society respecting the constitutional principles of publicity, efficiency, active transparency and speed in the process of administrative processes. The research sought to identify studies regarding the implementation of the electronic administrative process in various sectors of government, following the publication of the Law on Access to Information, which took place in 2011, also applying the provisions of Decree No. 8,539, 2015. The research is based on a qualitative approach using the bibliometric analysis methodology. The investigation concluded that the number of publications in the main academic research databases was deficient, considering the result of three articles referring to electronic administrative processes implemented in public administration. Therefore, it is suggested to investigate the use of other electronic means that deal with various work processes, but with a focus on transparency and efficiency of public services.